2014
DOI: 10.1371/journal.pone.0092239
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Analysis Using De Novo Transcriptome Assembly as a Reference for the Salmon Louse Caligus rogercresseyi

Abstract: Despite the economic and environmental impacts that sea lice infestations have on salmon farming worldwide, genomic data generated by high-throughput transcriptome sequencing for different developmental stages, sexes, and strains of sea lice is still limited or unknown. In this study, RNA-seq analysis was performed using de novo transcriptome assembly as a reference for evidenced transcriptional changes from six developmental stages of the salmon louse Caligus rogercresseyi. EST-datasets were generated from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 57 publications
(65 reference statements)
2
31
0
Order By: Relevance
“…Therefore, the observed changes occurred rapidly and had to rely either on a sufficiently large standing genetic variation of both host and parasite populations or on more plastic mechanisms like gene regulation. Similar to many other nonmodel organism transcriptome studies (e.g., Gallardo‐Escárate, Valenzuela‐Muñoz, & Nuñez‐Acuña, ; Patnaik et al., ; Qi et al., ; Yarra, Gharbi, Blaxter, Peck, & Clark, ), a significant proportion of assembled contigs could not be functionally annotated and we are aware that we may have missed novel functional aspects of co‐evolutionary interactions. Our results based on homology annotation revealed that the direct interaction between host and parasites can generate specificity of general responses (ROS pathways) on the transcription level within few generations, illustrating the value of invasive species for the study of host–parasite co‐evolution in nature.…”
Section: Resultssupporting
confidence: 67%
“…Therefore, the observed changes occurred rapidly and had to rely either on a sufficiently large standing genetic variation of both host and parasite populations or on more plastic mechanisms like gene regulation. Similar to many other nonmodel organism transcriptome studies (e.g., Gallardo‐Escárate, Valenzuela‐Muñoz, & Nuñez‐Acuña, ; Patnaik et al., ; Qi et al., ; Yarra, Gharbi, Blaxter, Peck, & Clark, ), a significant proportion of assembled contigs could not be functionally annotated and we are aware that we may have missed novel functional aspects of co‐evolutionary interactions. Our results based on homology annotation revealed that the direct interaction between host and parasites can generate specificity of general responses (ROS pathways) on the transcription level within few generations, illustrating the value of invasive species for the study of host–parasite co‐evolution in nature.…”
Section: Resultssupporting
confidence: 67%
“…Observations in distinct species of insects have shown that variations in cuticle thickness have a significant effect on susceptibility to insecticides (Vannini et al, 2014). Considering this, the present study was performed to determine if exposition to the antiparasitics azamethiphos and deltamethrin modulated transcriptional activity in C. rogercresseyi, with analysis focused on 479 contigs with high homology to genes involved in cuticle formation and identified through previously constructed genomic databases (Gallardo-Escárate et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…From the EST-database reported by Gallardo-Escárate et al (2014) for C. rogercresseyi, 63,444 high quality contigs were annotated according to Gene Ontology terms with the Blast2GO software (Conesa et al, 2005). Furthermore, tBLASTx analysis was performed against ESTdatasets downloaded from the NCBI for cuticle-related sequences reported for arthropod species.…”
Section: Rna-seq Analysis Of Cuticle-related Genes From C Rogercressmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was not until 2014 that Gallardo‐Escárate et al . () revealed the complete transcriptome modulation occurring in the copepod during ontogenetic development, highlighting several key features of the C. rogercresseyi life cycle that was previously unknown (Table ). The same study also revealed for the first time fundamental molecular differences between male and female adults, information that was only available at the time with EST collections for L. salmonis .…”
Section: Sea Louse: a “Hard To Kill” Parasitementioning
confidence: 92%